Tuning the sumanene receptor structure towards the development of potentiometric sensors. Issue 2 (14th December 2021) - Kasprzak, Artur; Tobolska, Aleksandra; Sakurai, Hidehiro; Wróblewski, Wojciech
Abstract : The structure of sumanene was tuned to enable its application as a receptor molecule in a potentiometric sensor for caesium cations detection. Abstract : Herein, we report for the first time the application of a sumanene derivative in potentiometric recognition of caesium cations. The structure of the sumanene receptor was carefully tuned to obtain its compatibility with polyvinyl chloride plasticized membranes of potentiometric sensors. The developed ion-selective electrodes based on membranes doped with octyloxybenzene sumanene exhibited a near theoretical sensitivity towards caesium cations, with a detection limit of 4 μM Cs + .